Investigation of glycolipids self-assemblies using fluorescence spectroscopy and small-angle X-ray scattering / Noor Idayu binti Mat Zahid - Mat Zahid, Noor Idayu (2013)
Glycolipids are one of the essential components of the cell membranes to carry out selected biological functions. Even though the study to resolve the ambiguity of biological membrane processes is continuously pursuit, it is now generally recognized that the lipids form lyotropic mesophases in the membranes. These phases are important biologically and technologically, thus our interest to characterize them. Herein, we investigate the microenvironment of various lipidic phases formed by mono- and dialkylated synthetic glycolipids using fluorescence technique. Both single and branched-chain synthetic glycolipids were observed to exhibit normal and inverse mesophases respectively. The polarity of different regions of the hydrophilic head group was estimated on the basis of a parallel study in different solvents using small fluorescent probes namely tryptophan (Trp) and two of its ester derivatives (Trp-C4 and Trp-C8). In contrast, the hydrophobic nature of pyrene is expected to favour the tail region of the self-assembly. The ratio of the two peak intensities (I1/I3) in the pyrene fluorescence spectra was used to elucidate the local environment of pyrene since it is environmentally sensitive. In addition, the lifetimes of all fluorescent probes in buffer and lipid were measured. We have also performed thermotropic and lyotropic investigations on four anomeric-epimeric related branched-chain glycolipids derived from Guerbet alcohols using small-angle X-ray scattering to obtain their detailed structural information as well as their partial binary phase diagram. Similar fluorescence study was carried out for one of these branched-chain glycolipids, which gave extensive inverse bicontinuous cubic phase. The results presented here are believed to be important for a better understanding of the glycolipids fundamental properties which may help uncover some biological mysteries.